A review of current metaverse applications as a tool for reshaping human behaviour in health communication - Md Ghani, Miharaini; Osman, Mohd Nizam; Omar, Siti Zobidah; Hanafi, Hafizul Fahri; Mustafa, Wan Azani; Shaiful Bakhtiar, Durratul Laquesha (Akademia Baru Publishing, 2024)
In line with the objectives of Industry 4.0, the Health 4.0 initiative promotes the integration of cutting-edge technology into medical practice. The Health 4.0 concept includes virtual reality (VR) as a component that has the potential to play an important role. Even though VR in the medical field is a hot issue right now, there is still a lack of understanding about VR-assisted treatment from a broad viewpoint. The combination of healthcare with the metaverse will result in more efficient resource distribution and usage within the healthcare system. The data pertaining to healthcare in the metaverse are kept on a public server, and Artificial Intelligence (AI)-based devices are used to retrieve it. Through the use of metaverse's healthcare systems, patients get a diagnosis in a timely manner. Because the metaverse is meant to be used for specific things, its effects on society, the economy, and culture are also determined by those things. The main findings of this review are to highlight the metaverse's goal of encouraging connectivity, collaboration, and new experiences directly affects how people interact, work, and interact with digital environments and how important it is for responsible and ethical development to make sure that all of these elements work well together. This analysis is going to be broken down into two distinct categories, the first two of which are purpose and impact. In conclusion, the findings of this research will help to improve strategic decision-making as well as policy-making processes in order to pursue the creation of commercial opportunities via the deployment of a metaverse service in healthcare and other comparable contexts.